Economic problems of agriculture in industrial societies : proceedings of a conference held by the International Economic Association - Papi, Ugo; Nunn, Charles (London : Macmillan : New York : St. Martin's P., 1969)
The book is a collective proceedings from contributor who attended the conference held by the International Economic Association.
Bibliographical footnotes.
gp. 24/01/2019
Loans
Keywords: Agriculture